Long non‐coding RNA‐H19 stimulates osteogenic differentiation of bone marrow mesenchymal stem cells via the microRNA‐149/SDF‐1 axis. Issue 9 (21st March 2020) - Li, Guangjie; Yun, Xiangdong; Ye, Kaishan; Zhao, Haiyan; An, Jiangdong; Zhang, Xueliang; Han, Xingwen; Li, Yanhong; Wang, Shuanke
Abstract: Bone defects resulting from non‐union fractures or tumour resections are common clinical problems. Long non‐coding RNAs (lncRNAs) are reported to play vital roles in stem cell differentiation. The aim of this study was to elucidate the role of lncRNA‐H19 in osteogenic differentiation of bone marrow mesenchymal stem cells (BMMSCs). Following the establishment of an osteogenic differentiation model in rats, the expression of H19, microRNA‐149 (miR‐149) and stromal cell‐derived factor‐1 (SDF‐1) was measured by RT‐qPCR. Thereafter, BMMSCs were isolated from rats and treated with a series of mimic, inhibitor or siRNA. SDF‐1 expression, alkaline phosphatase (ALP) activity and osteocalcin (OCN) content were detected. The mineralized and calcified nodules were assessed by alizarin red S and Von Kossa staining. BMMSC surface markers were detected by flow cytometry. Western blot analysis was used to measure the expression of ALP, OCN, runt‐related transcription factor 2 (RUNX2) and osterix (OSX) proteins. Lastly, dual‐luciferase reporter gene assay and RNA immunoprecipitation were applied to verify the relationship of H19, miR‐149 and SDF‐1. Overexpressed H19 and SDF‐1 and poorly expressed miR‐149 were found in rats with osteogenic differentiation. H19 increased SDF‐1 expression by binding to miR‐149. H19 enhanced ALP activity, OCN content, calcium deposit and ALP, OCN, RUNX2 and OSX protein expression of BMMSCS by up‐regulating SDF‐1 via binding to miR‐149. Taken together, up‐regulated H19 could promote the osteogenic differentiation of BMMSCs by increasing SDF‐1 via miR‐149.